Depicting history in the "novel chronicle" Sikmy kostel by Karin Lednicka - Mikesova, Iveta (Bohemica Olomucensia, 2023)
The article considers the role of historical fiction in Czech literature since the year 2000 and analyzes the depiction of history within the genre of family saga and novel chronicle based on the example of the first two volumes of Karin Lednicka's intended trilogy Sikmy kostel (2020, 2021).
Keywords: Czech literature; historical fiction; novel chronicle; family saga; Karin Lednicka